2000
DOI: 10.1074/jbc.c900990199
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Substitutions in κ-Conotoxin PVIIA Disrupt Interaction with the Shaker K+ Channel

Abstract: -Conotoxin PVIIA (-PVIIA), a 27-amino acid peptide with three disulfide cross-links, isolated from the venom of Conus purpurascens, is the first conopeptide shown to inhibit the Shaker K ؉ channel (Terlau, H., Shon, K., Grilley, M., Stocker, M., Stü hmer, W., and Olivera, B. M. (1996) Nature 381, 148 -151). Recently, two groups independently determined the solution structure for -PVIIA using NMR; although the structures reported were similar, two mutually exclusive models for the interaction of the peptide wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 28 publications
8
89
0
2
Order By: Relevance
“…1A). Sea Anemone-Sea anemones also have yielded a diversity of K ϩ channel peptide inhibitors classified into three main types (15 (20). A model of the -conotoxin PVIIA-Shaker K ϩ channel complex showed a reasonable correlation with experimental data (Fig.…”
Section: Potassium Channel Toxinsmentioning
confidence: 56%
“…1A). Sea Anemone-Sea anemones also have yielded a diversity of K ϩ channel peptide inhibitors classified into three main types (15 (20). A model of the -conotoxin PVIIA-Shaker K ϩ channel complex showed a reasonable correlation with experimental data (Fig.…”
Section: Potassium Channel Toxinsmentioning
confidence: 56%
“…5C). Similar overlays (not shown) can be made with the functionally critical diad residues in numerous other K ϩ channel blockers such as charybdotoxin (44) and -conotoxin PVIIA (45). Thus, although the three-dimensional fold of J-ACTX-Hv1c is homologous to the sodium channel modulators conotoxin GS, -agatoxin-I, and ␦-ACTX-Hv1a (12), the hot spot identified by site-directed mutagenesis provides circumstantial evidence that the J-ACTXs might target invertebrate K ϩ channels.…”
Section: Discussionmentioning
confidence: 97%
“…With the use of alanine-scanning mutagenesis, the interaction surface of -PVIIA with the Shaker channel pore has been identified. Mutations within the P-loop of the channel protein have major effects on the binding of -PVIIA (169); a double mutant cycling analysis revealed that -PVIIA, like other K channel blocking peptides, contains a critical dyad motif of amino acids important for K channel blockade (78). This dyad consists of lysine-7 and a phenylalanine-9, which are ϳ6 Å apart.…”
Section: -Conotoxinsmentioning
confidence: 99%